Epidermal growth factor receptor (EGFR) pathway polymorphisms as predictive markers of cetuximab toxicity in locally advanced head and neck squamous cell carcinoma (HNSCC) in a Spanish population. (December 2016) - Fernández-Mateos, J.; Seijas-Tamayo, R.; Mesía, R.; Taberna, M.; Pastor Borgoñón, M.; Pérez-Ruiz, E.; Adansa Klain, J.C.; Vázquez Fernández, S.; del Barco Morillo, E.; Lozano, A.; González Sarmiento, R.; Cruz-Hernández, J.J.; et al.
Highlights: EGFR overexpression is common in HNSCC, so a good target for therapeutic approaches. An association of KRAS-LCS6 (rs61764370) polymorphism with cetuximab toxicity was found. EGFR (rs2227983) variant showed a lower risk for pruritus after cetuximab treatment. KRAS (rs1801274) variant was significantly associated with lower cetuximab toxicity. Genetic variants related to reduced toxicity may allow allocation to other therapies. Abstract: Objectives: To examine the relationship between polymorphisms of the epidermal growth factor receptor (EGFR) pathway and toxicity in head and neck squamous cell carcinoma (HNSCC) patients treated with cetuximab. Material and methods: Multicenter, retrospective, observational pilot study which included 110 patients with histologically-confirmed human papillomavirus (HPV) negative HNSCC in locally advanced stages (III-IVA-B) and who were treated with chemotherapy and radiotherapy plus cetuximab between 2003 and 2013. Genetic analyses for single nucleotide polymorphisms (SNP) in genes EGFR, CCDN1, FCGR2A, FCGR3A and KRAS-LCS6 were performed though available allelic discrimination assay and/or polymerase chain reaction-restriction fragment length polymorphism methods. Results: Acneiform rash was observed in 55.5% of patients, dry skin in 45.5% and pruritus in 20.9%. A significant association with dry skin and global cetuximab-related toxicity was observed for the KRAS-LCS6 (rs61764370) variant (p < 0.05); carriers of the G allele (genotypes TG + GG) in the dominant model were observed to have a decreased susceptibility of developing dry skin (OR = 0.287 [95%CI = 0.119–0.695]). Carriers of the A (GA + AA) allele for EGFR (rs2227983) showed a decreased risk of suffering from pruritus (OR = 0.345 [0.124–0.958]). Similarly, KRAS (rs1801274) was related with lower global cetuximab-related toxicity (OR = 0.266 [0.114–0.622]). Conclusion: This pilot study provides preliminary evidence supporting genetic variation of EGFR (rs2227983), KRAS (rs61764370) and FCGR2A (rs180127) as useful biomarkers for predicting reduced skin toxicity in HNSCC patients treated with a cetuximab-based therapy. Alternative therapeutic options should be explored for these patients.